The Gradual Rise and Rapid Decline of the Middle Class in Latin America and the Caribbean - World Bank (World Bank, Washington, DC, 2021)
Latin America and the Caribbean (LAC) reported over 30 million Coronavirus (COVID-19) cases and around 960,000 deaths as of May 2021. Official tracking data shows that Brazil, Colombia, and Argentina have the highest number of reported cases throughout LAC, which in turn is the region with among the highest numbers across all developing regions. Moreover, Brazil is the third-worst affected country worldwide, after the United States and India, with approximately 15.4 million infections. Dramatic declines in economic activity are expected throughout the LAC region due to the global pandemic. Unfortunately, many LAC countries entered the crisis with low potential economic growth and high levels of inequality, following the region’s recent period of stagnant growth. The 2020 COVID-19 crisis will likely reverse in a short time frame many of the social gains that took decades to materialize in Latin America and the Caribbean. In the past two decades, the region has seen a reduction in the number of people living in poverty by nearly half and an increase in the size of its middle class. Income inequality also decreased, as income growth has been primarily pro-poor in recent years. Despite variations across countries, most have experienced positive welfare gains since the early 2000s. However, the growth deceleration of 2014–2019 coupled with the dramatic fall in activity caused by the COVID-19 crisis will negatively impact living standards and well-being across the region. Poverty projections for 2020 suggest that the number of the poor increased in most LAC countries. Brazil, however, implemented a generous emergency transfer program that benefited almost 67 million people and lifted millions out of poverty. As a result, poverty in the LAC region is expected to decline marginally from 22 percent in 2019 to 21.8 percent in 2020. Had no mitigation measures been implemented, the region may instead have seen 28 million new poor in 2020.